PENGARUH HARGA, BRAND IMAGE, PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA YUNA&CO DI JAKARTA PUSAT - Alma Dina Latansa, (2022)
This research is a quantitative study that examines social phenomena with the aim of analyzing and proving the effect of price, brand image, promotion on purchasing decisions. The research population is Yuna&Co consumers in the Central Jakarta area. This study took a sample of 100 respondents using a non-probability sampling technique with purposive sampling method. Data collection was carried out by distributing questionnaires to Yuna&Co consumers. The data analysis technique used is descriptive analysis and inferential analysis assisted by Partial Least Square (PLS) analysis tool in the form of SmartPLS 3.0. Hypothesis testing in this study is used by testing the coefficient of determination and t test using a significance level . The results of this study show that (1) the price variable has a positive and significant effect on purchasing decisions, (2) the brand image variable has a positive and significant effect on purchasing decisions and (3) the promotion variable has a positive and significant influence on purchasing decisions. .